HEALTH STATUS OF THE POPULATION OF KIROVOHRAD REGION UNDER THE INFLUENCE OF NATURAL LOW-INTENSIVE RADIATION - Сєрих, Наталя; Ракша-Слюсарева, Олена; Громова, Тетяна; Коваленко, Поліна; Коц, Сюзанна (SWorldJournal, 2022)
In today’s world, the impact of radiation on humans is no less important than the issues of drug addiction, alcoholism and AIDS. Radiation by its nature is harmful to life, namely it has a detrimental effect on human health. When radioactive radiation pa